1997
DOI: 10.1063/1.119017
|View full text |Cite
|
Sign up to set email alerts
|

Biaxially aligned buffer layers of cerium oxide, yttria stabilized zirconia, and their bilayers

Abstract: Biaxially aligned cerium oxide (CeO2) and yttria stabilized zirconia (YSZ) films were deposited on Ni-based metal (Hastelloy C276) substrates held at room temperature using ion beam assisted (IBAD) magnetron deposition with the ion beam directed at 55° to the normal of the film plane. In addition, we achieved, room-temperature epitaxial growth of CeO2 by bias sputtering to form biaxially aligned CeO2/YSZ bilayers. The crystalline structure and in-plane orientation of films was investigated by x-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…Thus, we assumed that the deposition rate differences could not affect the texturing of CeO 2 . The results are in agreement with Lee et al, who reported no significant changes in CeO 2 films when oxide targets are used (36), but mismatch with other processing techniques where it has been found a preferential texture in the (200) plane (37)(38)(39). The surface images of CeO 2 films using different experimental conditions without pretreatment were shown in Figure 3 a-d; whereas the effect of chemical pretreatment (NaOH and H 2 SO 4 ) on morphology and growth of CeO 2 thin films using different condition in the chamber are shown in Figure 3 e-h. From these figures, it can be seen that the sputtered CeO 2 displayed small round particles; this growth seems to follow the polish lines giving a uniform, porous and crack-free coating.…”
Section: Resultssupporting
confidence: 92%
“…Thus, we assumed that the deposition rate differences could not affect the texturing of CeO 2 . The results are in agreement with Lee et al, who reported no significant changes in CeO 2 films when oxide targets are used (36), but mismatch with other processing techniques where it has been found a preferential texture in the (200) plane (37)(38)(39). The surface images of CeO 2 films using different experimental conditions without pretreatment were shown in Figure 3 a-d; whereas the effect of chemical pretreatment (NaOH and H 2 SO 4 ) on morphology and growth of CeO 2 thin films using different condition in the chamber are shown in Figure 3 e-h. From these figures, it can be seen that the sputtered CeO 2 displayed small round particles; this growth seems to follow the polish lines giving a uniform, porous and crack-free coating.…”
Section: Resultssupporting
confidence: 92%
“…The substrates were bombarded with Ar ions at an angle of 55°from the substrate normal during the YSZ deposition to induce epitaxial growth. 21 The ion-beam assisted deposition produced smooth and dense films. 25 The substrates were mounted with the ͑110͒ planes oriented in the ion-beam direction which resulted in an epitaxial YSZ layer with MgO͑110͒ and YSZ͑110͒ planes aligned.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has been working on YBCO step-edge junctions and YBCO/YSZ superconducting tape in the past decade. 20,21 We started to investigate the fabrication of asymmetric 45°͓001͔ tilted grain boundary junctions by combining our techniques on making high-quality step edges and depositing high-quality YSZ to produce a bi-epitaxial junction. In this paper, we present fabrication techniques and measurements of 45°grain boundary junctions on MgO substrates using different thicknesses of YSZ as the seed layer.…”
Section: Introductionmentioning
confidence: 99%
“…IBAD has been used to produce biaxial textured thin films of Nb, 4 TiN, 5 MgO, 6 CeO 2 , 7 TiO 2 , 8 ZrN, 9 and yttria-stabilized zirconia ͑YSZ͒. While out-of-plane texture often occurs in thin films, 1 special measures such as off-axis ion beam assisted deposition ͑IBAD͒ 2 or an obliquely oriented sputter source 3 are needed to produce inplane texture.…”
Section: Introductionmentioning
confidence: 99%